Antifungal activity of Euphorbia species against moulds responsible of cereal ear rots - Jiménez, Cristina Marisol (2020)
This work aimed to identify secondary metabolites from aerial parts of Euphorbia species functional for control of toxigenic Fusarium species responsible of cereal grain rots. Methods and Results: Aerial parts of Euphorbia serpens, Euphorbia schickendantzii and Euphorbia collina were sequentially extracted with hexane, ethyl acetate and methanol. The extracts were tested against strains of Fusarium verticillioides and Fusarium graminearum by microdilution tests. The hexane extract of E. collina provided the lowest IC50s on both fungal species. Further fractionation showed that cycloartenol (CA) and 24-methylenecycloartanol are associated to the moderate inhibitory effect of the hexane extract on fungal growth.Sublethal concentrations of CA and 24MCA blocked deoxynivalenol (DON) and fumonisins production.CA and 24MCA co-applied with potassium sorbate, a food preservative used for Fusarium control, synergized the growth inhibition of fungi. The mixtures reduced mycotoxins accumulation when applied at sublethal concentrations. Conclusions: CA and 24MCA inhibited both fungal growth and mycotoxins production. This fact is an advantage respect to potassium sorbate which increased the mycotoxins accumulation at sublethal concentrations. Significance and Impact of the Study: CA and 24MCA synergized potassium sorbate and their mixtures offer a lower mycotoxigenic risk than potassium sorbate for control of the Fusarium species.